2015
DOI: 10.4028/www.scientific.net/amr.1134.185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Method on Thermal Behavior in PLA/PEG Melt Blending

Abstract: The dispersion of PEG acts as plasticizer in PLA blends were investigated using thermal analysis. The comparisons were made between two melt processing method, twin screw extruder and two-roll mills to study how it will affect theTg,TcandTmof blends in DSC analysis. The TGA behavior was also studied for two-roll mills processing method to confirm the effect of PEG loading in PLA on degradation and amount of residue left after analysis. In DSC analysis, it can be seen clearly, the PEG loading decreased the glas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In a study to analyze the miscibility of PLA and poly(butylene adipate-co-terphthalate) (PBAT), Dil and co-workers [39] used modulated DSC to determine one-way partial miscibility of PBAT in PLArich phases, which declines when a higher molecular weight PBAT is used in the blend. The thermal behavior of the polymeric blends also varies with the mode of preparation [40]. During blending, molecular mobility of the polymer changes, which eventually impacts Tg, crystallization, and corresponding enthalpies [41].…”
Section: Thermodynamics Of Blendsmentioning
confidence: 99%
“…In a study to analyze the miscibility of PLA and poly(butylene adipate-co-terphthalate) (PBAT), Dil and co-workers [39] used modulated DSC to determine one-way partial miscibility of PBAT in PLArich phases, which declines when a higher molecular weight PBAT is used in the blend. The thermal behavior of the polymeric blends also varies with the mode of preparation [40]. During blending, molecular mobility of the polymer changes, which eventually impacts Tg, crystallization, and corresponding enthalpies [41].…”
Section: Thermodynamics Of Blendsmentioning
confidence: 99%
“…The T g of PCL, PPDO, and PBA is −60 °C, −30 °C, and −42 °C, respectively. [44][45][46][47][48] Moreover, during heating, DHPMs exhibit convergent melting peaks at 48 °C, indicative of the substantial inuence of PEG on the functionalized segments. The melting temperatures (T m ) show varying degrees of decline, a characteristic of block copolymers, thus corroborating the favorable compatibility between PEG and the functional polymer chains.…”
Section: Compatibility Studies Of Chain Segmentsmentioning
confidence: 99%
“…Therefore, it was concluded that 30 wt.% PEG (A3) can effectively increase the plasticity of CPCMs [35], which is consistent with the SEM images. Compared with pure PLA, the addition of PEG lowered the melting point of the CPCMs, which was the result of PEG plasticization [36]. Tmo1 indicates the melting point onset temperature of the first peak; Tmp1 indicates the peak melting point temperature of the first peak; Tmo2 indicates the melting point onset temperature of the 2nd peak; Tmp2 indicates the peak melting point temperature of the 2nd peak; ∆Hm1 indicates the enthalpy of the 1st peak; ∆Hm2 indicates the enthalpy of the 2nd peak; ∆Hm = ∆Hm1 + ∆Hm2 (heat-absorbing melt peak, lower temperature for PEG melt, higher temperature for PLA melt).…”
Section: Phase Change Temperature and Latent Heatmentioning
confidence: 99%